Conceitualismo e lida absorvida: o debate entre John McDowell e Hubert Dreyfus - Daniel Mendes Campos Xavier Debarry (2018)
This thesis examined the so-called McDowell-Dreyfus Debate. The first chapter presents McDowell´s conceptualist thesis. The second chapter deals with the debate itself, having as background an analysis of the way Dreyfus reads phenomenologists such as Martin Heidegger and Maurice Merleau-Ponty in his attack on McDowell. In addition, it presents the way McDowell provides a response to Dreyfus based on the idea that concepts are in constant operation in perceptual experience. Contra Dreyfus, the third chapter presents conceptualist readings of Heidegger´s philosophy, as well as it strives to provide an approximation between McDowell and the German philosopher on the basis of the notion of normativity. We conclude our work showing certain possibilities of a middle ground to the debate.